Depressant Action of Alcohol Extract of Jasmine Root on Central Nervous System in Mice - Ning, Tian; Liang, Hong; Huang, Wen-Zhen; Duan, Xue-Lin; Peng, Yue; Zhao, Tie-Jian (Asian Journal of Chemistry, 2014)
The pharmacological effects on the central nervous system of the alcoholic extract of jasmine root were explored to elucidate the mechanism and provide experimental basis for the development and application of jasmine root. The independent activity determination method is applied to observe the drug sedation action and sodium pentobarbital synergy is taken to observe its hypnotic effect. Hot plate method and acetic acid-induced writhing method are used to observe the analgesic action. Alcohol extract of jasmine root decreased the independent activity of mice, which may indicated its sedative hypnotic effect. The synergistic effect with pentobarbital sodium may indicated its hypnotic effect. Alcoholic extract of jasmine root can reduce acetic acid-induced writhing times and increase pain threshold in mice, indicating its analgesic action. Alcoholic extract of jasmine root have sedative-hypnotic effect and the effect of analgesia in mice.